2006
DOI: 10.12693/aphyspola.110.537
|View full text |Cite
|
Sign up to set email alerts
|

Response of Grained La0.67Ca0.33MnO3Films to Microwave Radiation and the Method for Measuring Electrical Resistance of Grains

Abstract: It was found that the response of grained La0.67Ca0.33MnO3 films to microwave radiation is of thermal nature. A nonresonant method for measuring of the electric resistance of grains was developed. It allows one to avoid the influence of the magnetic field of the wave on the measurement results. The measurements of the temperature dependences of the grain electric resistance indicate that in the vicinity of the maximum-resistance temperature Tm, the intrinsic electric resistance of the grains is more than by tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The granules on the intergranular layer were distributed more or less uniformly i. e. the granule clusters were observed on the intergranular layer. Our measurements using microwave absorption technique show that intergranular layer resistance exceeds the resistance of granules itself by three order of magnitude [5]. Therefore, the size of the granules do not signicantly effect the total resistance of the layer.…”
Section: Experimental Investigations and Theoretical Modelmentioning
confidence: 66%
See 1 more Smart Citation
“…The granules on the intergranular layer were distributed more or less uniformly i. e. the granule clusters were observed on the intergranular layer. Our measurements using microwave absorption technique show that intergranular layer resistance exceeds the resistance of granules itself by three order of magnitude [5]. Therefore, the size of the granules do not signicantly effect the total resistance of the layer.…”
Section: Experimental Investigations and Theoretical Modelmentioning
confidence: 66%
“…The X-ray diffraction measurements demonstrated that so prepared films were single-phased and of pseudocubic perovskite structure and that the films on MgO (100) substrate were polycrystalline. Large dc resistance show polycrystalline character of the used films [1,5,6], too. The film surface was examined by atomic force microscope.…”
Section: Experimental Investigations and Theoretical Modelmentioning
confidence: 97%